Application of Dolomite and P Fertilizers Doses on The Growth and Yield of Edamame Soybean (Glycine max (L.) Merrill in Swampland - Anggraini, Septiana; Handayaningsih, Merakati; Haryanti, Yenda; Masdar; Marwanto; Setyowati, Nanik (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2023)
Pakchoy is a leafy vegetable that is great demand by Indonesians. The increase in population has had a major impact on agricultural land, which has encouraged an urban farming system, using polybags for crop production. The use of soil media in polybags often experiences compaction and lack of nutrients, so it is necessary to modify the composition of the planting media and put additional fertilization. This research was conducted to evaluate the response of pakchoy to local microorganisms based on rice waste and to determine the best composition of growing medium for pakchoy plants. This study used a completely randomized design (CRD) with 2 factors. The first factor was the local microorganism (LMO) doses of rice waste consisted of 4 levels, namely 0 ml, 500 ml, 1000 ml, and 1500 ml per plant. The second factor was the composition of the planting medium (Soil : Sand: Cow Manure) at 4 levels, namely Soil 100%, 1:1:1, 1:1:2, 1:1:3. Data were statistically analyzed with ANOVA at 5% level. Mean separation was tested further with Duncan Multiple Range Test. The results showed that the LMO 0 ml and 500 ml performed higher effects on plant height, number of leaves, plant fresh and dry weight, root fresh and dry weight, and root length compared to the application LMO at 1000 ml and 1500 ml. The highest plant fresh weight was 193.1 g at 0 ml LMO, followed by 160.35 g at 500 ml LMO. The composition of the planting medium 1:1:1 and 1:1:2 resulted in a higher number of leaves, plant dry weight, and root weight than other treatments. Incorporating a high portion of manure into the pakchoy planting medium was not beneficial. All growth variables and yield were higher compared to the control medium (soil 100%). Key Words: pakchoy, local microorganism, planting media